University Social Responsibility during The Covid-19 Pandemic: Lessons from the Indonesian Context - yeni rosilawati; Zain Rafique; Atik Septi Winarsih (Universitas Muhammadiyah Yogyakarta, 2022)
During the Covid-19 pandemic, social responsibility has become a key subject since it refers to the contribution of non-state actors in resolving the pandemic impact, becoming a non-traditional security issue. One non-state actor playing a significant role in society is educational institutions through university social responsibility (USR) programs. This study aims to analyze the form of USR programs and their benefits for communities affected by the pandemic. This study selected three universities as the case studies, encompassing Universitas Muhammadiyah Yogyakarta (UMY), Universitas Pertamina and Institut Pertanian Bogor (IPB). During the Covid-19 pandemic, these three universities implemented USR in the social field under the triple bottom line concept. This research employed in-depth interviews and secondary data collected through website reviews and clippings from the mass media. The results unveiled that UMY, Universitas Pertamina and IPB implemented USR in community empowerment in education, health, and technological innovation. These three universities established community empowerment schemes by involving students, lecturers and other stakeholders to demonstrate their contribution to dealing with and solving community problems caused by the pandemic. These three universities have always been oriented toward innovation, especially in education, research and community service. Innovation is significant because it helps increase skills, add value to the wider community, and impact sustainable development.